The Influence Of Financial Literacy And Self-Control On Financial Management Of Unpab Management Students Stambuk 2022 - Salwida Nasution; Ramadhan Harahap; Noni Ardian (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of financial literacy and self-control on the financial management of students in the Management Study Program of Panca Budi Development University (UNPAB) class of 2022. This type of research is quantitative with a survey approach. The study population was active management students of Panca Budi Development University, batch 2022. The sampling technique used purposive sampling, obtaining 77 students. The research instrument was a questionnaire with a Likert scale. The data analysis method used multiple linear regression analysis with the IBM SPSS 27 application. Financial literacy has a positive and significant effect on student financial management. Self-control has a positive and significant effect on student financial management. Financial literacy and self-control simultaneously have a significant effect on financial management of students in the Management Study Program of Panca Budi Development University, batch 2022. This study was limited to students in the Management Study Program of Panca Budi Development University, so the results cannot be generalized to all students in Indonesia. The variables studied were limited to financial literacy and self-control, while there are still other variables that can influence effective student financial management. This study contributes to the development of financial management science, especially in the field of financial literacy and student financial behavior. The research findings can provide input for universities in designing financial education programs to improve students' financial management skills. This research contributes to the development of financial management science, particularly in the areas of financial literacy and student financial behavior. The research findings can provide input for universities in designing financial education programs to improve students' financial management skills..